Determination of quality kinetics, microbiology, and sensory properties of shelf-stable chicken-wing sauce - Purohit, Anuj; Jain, Mahima; Sarkhel, Shubhajit; Roy, Anupam; Mohan, Anand (Frontiers in Food Science and Technology, 2023)
The development of shelf-stable foods is necessary to reduce dependence on refrigeration during their storage and distribution. Current trends in shelf-stable foods have seen a continuous rise in consumer demand that triggers research studies in the formulation, shelf stability, processing, and manufacturing of sauces frequently used by the food service industry. This study evaluated the shelf-life stability of chicken wing sauce with different flavors (hot, lemon pepper, sweet chili, teriyaki, and mild). All sauce formulations were developed and thermally processed to pasteurize using the hot-fill-and-hold (87.75 ℃ for 5 min) method in a portable container which was then kept at ambient temperature (18.35 ℃ ± 2) for 12 months. The samples were drawn periodically and analyzed for color, rheology, sensory, and microbial load. The study’s findings revealed that sauces with different flavors (hot, lemon pepper, sweet chili, teriyaki, and mild) significantly declined in color and appearance, including viscosity, after ten months of storage. A very similar trend was noticed in textural changes. With the advancement of storage time, textural changes became prominent in lemon pepper and sweet chili sauce compared to hot teriyaki and mild sauces. Microbial analyses indicated the absence of pathogenic organisms, and no microbial activity was observed throughout the storage for up to 12 months. Among all sauces studied in this research project, lemon pepper exhibited a drastic decline in flavor, including some rancidity development after seven months of storage. Extension of the shelf life and overall quality of the most commonly used sauces in the food service industry is of paramount importance. A better understanding of the changes in the physicochemical properties of sauces during storage can help food processors understand the expected changes.